Restoring Image and Identity of Old City Kupang Through Visual Enhancement - Paulus Kusuma Dewata Hoka Djoka; Arina Hayati; Endang Titi Sunarti (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
The old city in Kupang is a dense area that has multicultural ethnicity with its history. With long historical background influenced by colonialism and multicultural diversity, the old city of Kupang has strong and unique images. This paper aims to find the image and the identity of the old city area in Kupang supported by using factors in Lynch’s theory of image of the city. This research using descriptive-qualitative research method and applied several data collection techniques such as field observation through walkthrough analysis and documentation. The research method has successfully identified the old city’s image and identity; (1) Soekarno Street and Siliwangi Street as the path element; (2) meeting point of main streets and streets around the old city area including Soekarno and Siliwangi street as nodes element; (3) Pancasila Monument identified as landmark element. The result of this study is important as a reference to enhance the visual quality of Kupang old city by strengthening the character of the image and identity of the old city area.